A Review of Multi-Port DC-DC Converter Research - He, Caiyi (International Journal of Mechanical and Electrical Engineering, 2024)
In modern power electronics and energy management systems, multi-port DC-DC converters are of excellent research significance as they can meet the demands of multiple energy inputs and multiple load outputs in complex systems. With the increasing complexity of energy systems, traditional single-port and bi-directional DC-DC converters make it challenging to meet these demands, so it has become necessary to develop multi-port DC-DC converters for efficient and flexible energy management. The direction of this research mainly reviews the research background and current status of multi-port DC-DC converters, discusses their applications in renewable energy systems, hybrid vehicles, and microgrids, and proposes future research directions.